2017
DOI: 10.1016/j.ejphar.2017.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco's minor alkaloids: Effects on place conditioning and nucleus accumbens dopamine release in adult and adolescent rats

Abstract: Tobacco products are some of the most commonly used psychoactive drugs worldwide. Besides nicotine, alkaloids in tobacco include cotinine, myosmine, and anatabine. Scientific investigation of these constituents and their contribution to tobacco dependence is less well developed than for nicotine. The present study evaluated the nucleus accumbens dopamine-releasing properties and rewarding and/or aversive properties of nicotine (0.2-0.8mg/kg), cotinine (0.5-5.0mg/kg), anatabine (0.5-5.0mg/kg), and myosmine (5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…This call profile shift suggests that high-dose nornicotine may be aversive, but whether nornicotine also produces a conditioned place or taste aversion appears unreported. Cotinine is reportedly neutral in the conditioned place preference/aversion assay (Fudala and Iwamoto 1986;Marusich et al 2017), so its lack of effect on call profile (present study) is perhaps to be expected.…”
Section: Effects Of Drugs Alone On Call Rate and Call Profilementioning
confidence: 68%
See 1 more Smart Citation
“…This call profile shift suggests that high-dose nornicotine may be aversive, but whether nornicotine also produces a conditioned place or taste aversion appears unreported. Cotinine is reportedly neutral in the conditioned place preference/aversion assay (Fudala and Iwamoto 1986;Marusich et al 2017), so its lack of effect on call profile (present study) is perhaps to be expected.…”
Section: Effects Of Drugs Alone On Call Rate and Call Profilementioning
confidence: 68%
“…Under the same conditions, cotinine did not detectably alter LMA. To our knowledge, acute locomotor effects of cotinine have only been reported in drugnaive rats, with only equivocal signs of locomotor depression (Marusich et al 2017;Wiley et al 2015).…”
Section: Effects Of Drugs Administered Alone On Locomotor Activitymentioning
confidence: 89%
“…However, baseline dopamine level in tissue samples of NAc and frontal cortex was reported to be comparable between adolescent and adult rats [ 60 ]. Furthermore, nicotine has been shown to increase dopamine release in the NAc in both adults and adolescent rats [ 62 ]. On the other hand, repeated ethanol administration in mice resulted in sensitization only in adults but not adolescents [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cotinine-mediated dopamine release is blocked by the nicotine receptor antagonists mecamylamine and dihydro-beta-erythroidine (Dwoskin et al, 1999). However, nicotine, but not cotinine, stimulates the release of dopamine in the nucleus accumbens in adolescent and adult rats (Benwell and Balfour, 1992; Marusich et al, 2017). Studies with rodents have shown that nicotine has stimulatory and rewarding effects.…”
Section: Animal Models Of Nicotine Withdrawal Symptomsmentioning
confidence: 99%